2005
DOI: 10.1897/04-093r.1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microbial metabolism in anaerobic lagoons by selected sulfonamides, tetracyclines, lincomycin, and tylosin tartrate

Abstract: Antibiotics are used to maintain healthy livestock and to promote weight gain in concentrated animal feed operations. Antibiotics rarely are metabolized completely by livestock and, thus, are often present in livestock waste and in waste-treatment lagoons. The introduction of antibiotics into anaerobic lagoons commonly used for swine waste treatment has the potential for negative impacts on lagoon performance, which relies on a consortium of microbes ranging from fermentative microorganisms to methanogens. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 38 publications
0
57
1
Order By: Relevance
“…Swine wastewater is a highly complex mixture consisting of proteins, carbohydrates, fats as well as various inorganic species [25]. On account of the significant matrix influence in the swine wastewater and diverse chemical properties of the nine antibiotics, an effective and simultaneous extraction of all the antibiotics was difficult to achieve.…”
Section: Optimization Of Spementioning
confidence: 99%
See 1 more Smart Citation
“…Swine wastewater is a highly complex mixture consisting of proteins, carbohydrates, fats as well as various inorganic species [25]. On account of the significant matrix influence in the swine wastewater and diverse chemical properties of the nine antibiotics, an effective and simultaneous extraction of all the antibiotics was difficult to achieve.…”
Section: Optimization Of Spementioning
confidence: 99%
“…Table 6 shows that except SML, all the other eight antibiotics were detected in different swine wastewaters with concentrations ranging from 0.62 to 32.67 g/L. Tetracyclines were detected in all the three swine wastewaters with relatively high concentrations (e.g., 25.36 g/L OTC in the Shunyi wastewater and 32.67 g/L CTC in the Haidian wastewater), implying that tetracyclines may be most commonly used in Beijing CAFOs. This agrees well with our survey information.…”
Section: Concentrations Of Antibiotics In Typical Cafos In Beijing Areamentioning
confidence: 99%
“…Previous studies of macrolide inhibition in anaerobic systems provide contradictory results, ranging from negligible effects (Camprubi et al, 1988;Chelliapan et al, 2006;Masse et al, 2000;Poels et al, 1984;Stone et al, 2009) to substantial decreases in treatment performance (Amin et al, 2006;Loftin et al, 2005;Sanz et al, 1996;Shimada et al, 2008a). In anaerobic batch tests, the addition of tylosin has inhibited acetate, propionate, and butyrate uptake (Amin et al, 2006;Sanz et al, 1996;Shimada et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the inhibitory effects of tylosin on anaerobic treatment performance (pH levels from 6.9 to 7.8) appear contradictory (Angenent et al, 2008;Chelliapan et al, 2006;Loftin et al, 2005;Masse et al, 2000;Poels et al, 1984;Sanz et al, 1996). Studies of ASBRs treating swine manure indicated that the addition of tylosin to the influent (up to 16.7 mg/L) had negligible effects on methane production and chemical oxygen demand (COD) removal efficiency (Angenent et al, 2008;Masse et al, 2000;Poels et al, 1984).…”
Section: Introductionmentioning
confidence: 99%